Islam 9/11 and Global Terrorism: A study of Perceptions and solutions - Islam, Nazrul (New Delhi, 2005)
Islam 9/11 and Global Terrorism is a brilliant exposition of a growing perception that post 9/11 more Muslims are taking to terrorism. It is a pioneering attempt to comprehensively examine this issue right from the theological origins of political Islam to Islamic faith, beliefs and tradition, from what motivates a terrorist, to the concept of Jihad versus the concept of tolerance.
Keywords: Terrorism